Comparing Walking age, Receptive and Expressive Language Profiles between Speech Delay Children with and without Hearing Loss - Aulia Sakinah; Nyilo Purnami, Thtkl K; Nuniek Nugraheni S; Sulistiawati (Institute of Medico-legal Publications Pvt Ltd, 2022)
Objectives : The study aimed to investigate whether walking age, receptive, and expressive languageprofiles differ between speech delay children with hearing loss and speech delay children withouthearing loss; to identify walking age, receptive, and expressive profiles between speech delay childrenwith hearing loss and speech delay children without hearing loss.Methods : The study is an observational analytic with retrospective cross-sectional design usingmedical records data for two years. Data was collected using a total sampling technique.Results : The study involved 92 children with speech delay, consisting 72 children in the hearing lossgroup and 20 children in the normal hearing group. The average age at walk as gross motoric profileshows that speech delays children with hearing loss have an average age that is later than speech delayschildren without hearing loss. Also, walking age significantly differs between children with speechdelay in hearing loss group and normal hearing group. Both receptive and expressive language profilesshow no different between the groups.Conclusions : Findings have consequences for consideration motor developmental delay in children withspeech delay, especially in hearing loss group. So that, the findings can be a reference to considerationin further management basis for speech delay interventions with and without hearing loss in children.